1981
DOI: 10.1159/000299602
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Glycine on Serum Gonadotropins and Estradiol and on Concentrations of Free Amino Acids in the Middle Hypothalamus in Female Rats

Abstract: The effects of glycine on serum gonadotropins and estradiol (E2) and on concentrations of free amino acids in the middle hypothalamus have been studied in diestrus-1 rats. 20 min after intraperitoneal administration, glycine in doses of 50 and 100 mg had no significant effect on serum luteinizing hormone (LH) levels, but 200 mg significantly elevated serum LH levels. Glycine in doses of 50–200 mg had no effect on serum follicle-stimulating hormone levels at 20 min after intraperitoneal injection. 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…12,53,54 In contrast to our findings above, Petzke et al 36 reported no significant differences in the δ 13 C and δ 15 N values of individual AAs from hair of a large cohort of German subjects. Regarding the significant effect of Gly in our work, Morishita et al 55 suggested that, in female rats, Gly is involved in the neural regulation of luteinizing hormone (LH) excretion. This hormone is directly related to male and female sex hormones, working in biochemical pathways that lead to the production and release of estrogen and testosterone.…”
Section: ■ Results and Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…12,53,54 In contrast to our findings above, Petzke et al 36 reported no significant differences in the δ 13 C and δ 15 N values of individual AAs from hair of a large cohort of German subjects. Regarding the significant effect of Gly in our work, Morishita et al 55 suggested that, in female rats, Gly is involved in the neural regulation of luteinizing hormone (LH) excretion. This hormone is directly related to male and female sex hormones, working in biochemical pathways that lead to the production and release of estrogen and testosterone.…”
Section: ■ Results and Discussionmentioning
confidence: 62%
“…Studies involving sex and stable isotopes are often related to dietary differences linked to social identity status in the organization of ancient societies. The limited publications in this field suggest that sex differences do not interfere with the bulk isotope values. ,, In contrast to our findings above, Petzke et al reported no significant differences in the δ 13 C and δ 15 N values of individual AAs from hair of a large cohort of German subjects. Regarding the significant effect of Gly in our work, Morishita et al suggested that, in female rats, Gly is involved in the neural regulation of luteinizing hormone (LH) excretion. This hormone is directly related to male and female sex hormones, working in biochemical pathways that lead to the production and release of estrogen and testosterone.…”
Section: Resultsmentioning
confidence: 99%